Massive bloody pericardial effusion as an initial manifestation of chronic kidney disease - Fazel, Poorya (Baylor Health Care System, 2013)
We describe a 35-year-old man with a massive bloody pericardial effusion, which was his initial manifestation of chronic kidney disease. Pericardiocentesis and hemodialysis restored cardiac function and relieved the associated massive anasarca.